Transposon mutagenesis in Proteus mirabilis. - Belas, R (1991)
A technique of transposon mutagenesis involving the use of Tn5 on a suicide plasmid was developed for Proteus mirabilis. Analysis of the resulting exconjugants indicated that Tn5 transposed in P. mirabilis at a frequency of ca. 4.5 x 10(-6) per recipient cell. The resulting mutants were stable and retained the transposon-encoded antibiotic resistance when incubated for several generations under nonselective conditions. The frequency of auxotrophic mutants in the population, as well as DNA-DNA hybridizaiton to transposon sequences, confirmed that the insertion of the transposon was random and the Proteus chromosome did not contain significant insertional hot spots of transposition. Approximately 35% of the mutants analyzed possessed plasmid-acquired ampicillin resistance, although no extrachromosomal plasmid DNA was found. In these mutants, insertion of the Tn5 element and a part or all of the plasmid had occurred. Application of this technique to the study of swarmer cell differentiation in P. mirabilis is discussed.